2007
DOI: 10.1029/2006jd008105
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving surface parameters for climate models from Moderate Resolution Imaging Spectroradiometer (MODIS)‐Multiangle Imaging Spectroradiometer (MISR) albedo products

Abstract: [1] We present a computer-efficient software package enabling us to assimilate operational remote-sensing flux products into a state-of-the-art two-stream radiation transfer scheme suitable for climate models. This package implements the adjoint and Hessian codes, generated using automatic differentiation techniques, of a cost function balancing (1) the deviation from the a priori knowledge on the model parameter values and (2) the misfit between the observed remote-sensing fluxes and the two-stream model simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 42 publications
0
57
0
Order By: Relevance
“…A number of studies has demonstrated that exploiting multi-angular information of MISR can improve retrieval of LAI and FAPAR [28][29][30][31]. One physically-based approach for deriving FAPAR from 275 m is the JRC-TIP approach that uses MISR resolution data [32,33] to invert a radiative transfer model. This package is based on a two-stream model [34] and uses prior information to constrain the RT model inversion.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has demonstrated that exploiting multi-angular information of MISR can improve retrieval of LAI and FAPAR [28][29][30][31]. One physically-based approach for deriving FAPAR from 275 m is the JRC-TIP approach that uses MISR resolution data [32,33] to invert a radiative transfer model. This package is based on a two-stream model [34] and uses prior information to constrain the RT model inversion.…”
Section: Introductionmentioning
confidence: 99%
“…Pinty et al (2008) apply the same strategy but to high-and midlatitude sites, as their focus lies on the behaviour of JRC-TIP products in the presence of snow. MISR is an instrument flying on the same platform (called Terra) as one of the MODIS instruments, and the procedure for deriving a WSA comparable to the standard MODIS product is described by Pinty et al (2007). As MISR observes each pixel from several angles, it can collect a high number of samples and thus provide a good angular integral of reflectance, i.e.…”
Section: Validationmentioning
confidence: 99%
“…For example, Pinty et al (2007) analyse differences between JRC-TIP products derived from MODIS and MISR broadband WSAs. Pinty et al (2008) apply the same strategy but to high-and midlatitude sites, as their focus lies on the behaviour of JRC-TIP products in the presence of snow.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…All parameters were taken from the Joint Research Centre Two-stream Inversion Package (JRC-TIP) (Pinty et al, 2011a, b). This is a software package (Pinty et al, 2007) which inverts a two-stream model (Pinty et al, 2006) to best fit the MODIS broadband visible and near-infrared white sky surface albedo from 2001 to 2010 at 1 km resolution (Pinty et al, 2011a). The inverse procedure implemented in the JRC-TIP is shown to be robust, reliable, and compliant with large-scale processing requirements (Pinty et al, 2011a).…”
Section: Multi-layer Two-way Radiation Scheme For Tall Canopiesmentioning
confidence: 99%